Development and validation of the compulsive-buying follow-up scale: A measure to assess treatment improvements in compulsive buying disorder. (December 2019) - Nicoli de Mattos, Cristiana; S Kim, Hyoun; Zambrano Filomensky, Tatiana; Tavares, Hermano
Highlights: The currently existing instruments used to measure improvement in Compulsive Buying Disorder have several limitations. The Compulsive Buying Follow-up Scale is a self-assessment scale with six items of multiple-choice regarding compulsive buying in the past 4 weeks. The scale's global alpha was high as well as the item-total correlations per item and the estimations of alpha if-item-delete were all under the global alpha value. The correlations pre- and post-treatment, between the BFS and the scales of reference for CBD showed a strong correlation with almost all reference scales. The scale had good sensibility to change and accuracy. Abstract: The aim of the present research was to develop a scale to assess treatment improvements for compulsive buying disorder (CBD), adapted from the Gambling Follow-up Scale Self-Report Version. The Compulsive Buying Follow-up Scale (CBFS) contains six self-report multiple-choice items assessing different aspects of compulsive buying in the past four weeks. Forty-eight treatment-seeking patients with CBD were evaluated, with 39 patients completing the 12-week follow-up. The scale's global alpha was high as well as the item-total correlations per item. The estimations of alpha if-item-deleted were all under the global alpha value, indicating that all items provided relevant contribution within the scale. The CBFS demonstrated significant correlations with previously developed scales of CBD and other measures of psychopathology, with the exception of a non-significant association with the Beck Depression Inventory at pre-treatment. The CBFS correlated significantly with all reference scales at post-treatment. The CBFS also demonstrated strong sensitivity to change and recovery status. The cutoff for the CBFS that provided the greatest sensitivity (0.93) and specificity (0.82) was 22. The results provide support that CBFS is a reliable and valid instrument to measure treatment outcomes over time for CBD.